2012
DOI: 10.1128/aac.06378-11
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle X-Ray Scattering Analysis of the Bifunctional Antibiotic Resistance Enzyme Aminoglycoside (6′) Acetyltransferase-Ie/Aminoglycoside (2″) Phosphotransferase-Ia Reveals a Rigid Solution Structure

Abstract: Aminoglycoside (6=) acetyltransferase-Ie/aminoglycoside (2؆) phosphotransferase-Ia [AAC(6=)-Ie/APH(2؆)-Ia] is one of the most problematic aminoglycoside resistance factors in clinical pathogens, conferring resistance to almost every aminoglycoside antibiotic available to modern medicine. Despite 3 decades of research, our understanding of the structure of this bifunctional enzyme remains limited. We used small-angle X-ray scattering (SAXS) to model the structure of this bifunctional enzyme in solution and to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…23,24 Sulfonamides 39 and 46 did not inhibit KAN acetylation by the AACs tested at concentrations as high as 200 μ M, with the exception of 39 , which inhibited 15% of the AAC(2′)-Ic activity when tested at 200 μ M. These data demonstrate the high selectivity of our inhibitors toward Eis.…”
Section: Resultsmentioning
confidence: 64%
“…23,24 Sulfonamides 39 and 46 did not inhibit KAN acetylation by the AACs tested at concentrations as high as 200 μ M, with the exception of 39 , which inhibited 15% of the AAC(2′)-Ic activity when tested at 200 μ M. These data demonstrate the high selectivity of our inhibitors toward Eis.…”
Section: Resultsmentioning
confidence: 64%
“…In early attempts to understand the role and impact of domain interactions of bifunctional AMEs on antibiotic resistance, Wright and co-workers demonstrated that a connecting α-helix between the two domains of the fused AAC(6′)-Ie/APH(2″)-Ia was critical to maintain both correct structure and function of both domains [21]. More recently, by using small-angle X-ray scattering to model the structure of this bifunctional enzyme, Berghuis and co-workers concluded that AAC(6′)-Ie/APH(2″)-Ia adopts a rigid conformation in solution, which likely contributes to improvement of the enzymatic activities of the individual enzymes [22]. By revisiting the nucleotide and AG substrate specificity of this bifunctional enzyme, Vakulenko and co-workers recently reported that, contrary to previous beliefs, GTP is the exclusive phosphate donor in cells for this enzyme [9].…”
Section: Resultsmentioning
confidence: 99%
“…5A). Also, bifunctional enzymes, such as AAC(6′)-Ie/APH(2″)-Ia from Staphylococcus aureus , 109112 AAC(3)-Ib/AAC(6′)-Ib′ from P. aeruginosa , 113, 114 ANT(3″)-Ii/AAC(6′)-IId from Serratia marcescens , 115117 and AAC(6′)-30/AAC(6′)-Ib from P. aeruginosa 118, 119 exist and are capable of multiple types of AG modification. AAC(6′)-Ib is the most prevalent and clinically relevant AME; approximately fifty variants of AAC(6′)-Ib exist in numerous Gram-negative species.…”
Section: Ag-modifying Enzymesmentioning
confidence: 99%